G293(P) Towards emergency triage assessment and treatment (ETAT)++: introducing basic paediatric trauma management skills in rural ghana. (May 2019) - James, DR; Barling, J; Ross, O; Daniel, AA; Crocker, C; Jarvis, E; Alexander, B
Abstract : Aims: ETAT is an internationally recognised course on the care of acutely unwell children delivered in resource poor settings. ETAT has subsequently evolved to ETAT+to include admission care. Injuries are the commonest cause of death in children, over one year old, worldwide and form an increasing proportion of child death in resource poor settings with no internationally recognised paediatric specific trauma course designed to address this. We aimed to introduce and evaluate one module of trauma teaching alongside standard a standard ETAT +course in the Upper East Region of Ghana. Methods: A course was planned and conducted in May 2018 and delivered to 30 participants (physician assistants, nurses and midwives) through the Ghana AfriKids Southampton (GAS) Partnership. Pre, immediate post and 8 week post course questionnaires assessed confidence and knowledge in management of acutely ill children, injured children and sick/premature babies. Each was conducted on a 5-part Likert scale. Data was analysed on Microsoft excel. Results: We received pre and immediate post course feedback from 29/30 delegates. Initial self reported knowledge was lower in injuries compared to illness (3.86 v 4.1). Confidence and knowledge increased in all domains. The biggest increases in immediate post course confidence and knowledge compared with pre course were in injury management (4.21 v 3.8 and 4.24 v 3.8). We received further feedback at 8 weeks from 16/30 participants. Average knowledge and confidence remained improved from baseline in all domains as shown in the table 1 below. Discussion: This work highlights the need for clinicians working in acute paediatric services in resource poor settings to receive training in the treatment of acutely injured children. It demonstrates that the simple addition of a trauma module to ETAT+can lead to continued improvement in knowledge and confidence in this area. This work should provde a stimulus to the further development of resource poor setting specific child trauma training.